2019
DOI: 10.1111/1752-1688.12792
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Nitrogen Transport in the Binational Great Lakes Basin Estimated Using SPARROW Watershed Models

Abstract: Eutrophication problems in the Great Lakes are caused by excessive nutrient inputs (primarily phosphorus, P, and nitrogen, N) from various sources throughout its basin. In developing protection and restoration plans, it is important to know where and from what sources the nutrients originate. As part of a binational effort, Midcontinent SPARROW (SPAtially Referenced Regression On Watershed attributes) models were developed and used to estimate P and N loading from throughout the entire basin based on nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The BRE technique was shown to produce more accurate and less biased long‐term mean‐annual loads than the regression techniques previously used for less conservatively transported constituents, such as P that was believed to be underestimated (Lee et al 2016). Robertson et al (2019) also showed that using the modified BRE technique for sites without trends (some sites included in this study) improved load estimation and that the use of those loads improved SPARROW model accuracy. Robertson et al (2019) also showed that most calibration sites were in areas without point sources, and the improved (increased) P loads in these areas resulted in nonpoint sources being more important and point sources (WWTPs) being less important.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The BRE technique was shown to produce more accurate and less biased long‐term mean‐annual loads than the regression techniques previously used for less conservatively transported constituents, such as P that was believed to be underestimated (Lee et al 2016). Robertson et al (2019) also showed that using the modified BRE technique for sites without trends (some sites included in this study) improved load estimation and that the use of those loads improved SPARROW model accuracy. Robertson et al (2019) also showed that most calibration sites were in areas without point sources, and the improved (increased) P loads in these areas resulted in nonpoint sources being more important and point sources (WWTPs) being less important.…”
Section: Discussionmentioning
confidence: 51%
“…Robertson et al (2019) also showed that using the modified BRE technique for sites without trends (some sites included in this study) improved load estimation and that the use of those loads improved SPARROW model accuracy. Robertson et al (2019) also showed that most calibration sites were in areas without point sources, and the improved (increased) P loads in these areas resulted in nonpoint sources being more important and point sources (WWTPs) being less important.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The transboundary nature of the watershed has complicated efforts to trace N pollutant sources in air and waters and to develop effective nutrient management plans. However, construction of a transboundary total N budget allows us to integrate information from all sectors, compare different management practices across the border (Robertson et al, 2019), and link these activities to the environmental outcomes. An informal partnership formed in 2016 between scientists and stakeholders in the United States and Canada to study N budgets and sustainability for the transboundary watershed.…”
Section: Introductionmentioning
confidence: 99%